The wearable cardioverter defibrillator as a bridge to reimplantation in patients with ICD or CRT-D-related infections. Issue 1 (December 2017) - Castro, L.; Pecha, S.; Linder, M.; Vogler, J.; Gosau, N.; Meyer, C.; Willems, S.; Reichenspurner, H.; Hakmi, S.
Abstract Background The approach to treat device infection in patients with implantable cardioverter defibrillator (ICD) or cardiac resynchronization therapy defibrillator (CRT-D) is a challenging procedure. Optimal treatment is complete extraction of the infected device. To protect these patients from sudden cardiac arrest while waiting for reimplantation and to avoid recurrent infection, a wearable cardioverter defibrillator (WCD) seems to be a valuable solution. Therefore, we investigated the management and outcome of patients with ICD or CRT-D infections using the WCD as a bridge to re-implantation after lead extraction procedures. Methods We conducted a retrospective study on consecutive patients who underwent ICD or CRT-D removal due to device-related local or systemic infections. All patients were prescribed a WCD at our center between 01/2012 and 10/2015. All patients returned to our outpatient clinic for regular ICD or CRT-D monitoring initially 1 and 3 months after reimplantation followed by 6-months intervals. Results Twenty-one patients (mean age 65.0 ± 8.0 years, male 76.2%) were included in the study. Complete lead extraction was achieved in all patients. While waiting for reimplantation one patient experienced a symptomatic episode of sustained ventricular tachycardia. This episode was converted successfully into sinus rhythm by a single 150 J shock. Mean follow-up time 392 ± 206 days, showing survival rate of 100% and freedom from reinfection in all patients. Conclusion The WCD seems to be a valuable bridging option for patients with ICD or CRT-D infections, showing no recurrent device infection.